An electrode and its preparation method and application

Through the method of low-temperature heating treatment and soaking of bimetallic salt mixed solution, the problem of the metal substrate pretreatment in the prior art requires a large amount of acid and alkali, solvent-free cleaning and efficient catalyst growth are achieved, and the electrolytic oxygen analysis activity of the electrode is improved. .

CN116815223BActive Publication Date: 2025-02-07CRINM (GUANGDONG) INST FOR ADVANCED MATERIALS & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311026656.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-07
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

The pretreatment methods of existing metal substrates require a large amount of acid and alkali, which is difficult to operate on a large scale, and commonly used cleaning methods waste solvents, making it difficult to remove organic matter and oxide layers on large areas of substrates.

Method used

The metal substrate was treated with low temperature heat, and the surface organic matter was removed to retain the oxide layer. Then, the bimetallic salt mixture was soaked at room temperature to grow the bihydroxide nanosheet catalyst in situ.

Benefits of technology

This method can simply and without solvents to remove organic matter from the metal substrate and activate the substrate. The grown catalyst has a high specific surface area and good catalytic activity, which improves the electrolytic oxygen analysis activity and stability of the anode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116815223B_ABST
    Figure CN116815223B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of hydrogen energy material preparation, and discloses an electrode and its preparation method and application, comprising the following steps: placing a metal substrate in a heating device, heating at a low temperature in a calcining atmosphere, keeping the temperature, cooling naturally, washing with water and drying to obtain the activated metal substrate. The activated metal substrate is placed in a mixed solution of a double metal salt, and a double hydroxide nanosheet catalyst is grown in situ on the activated metal substrate. The electrode prepared by the preparation method of the present application has a better oxygen evolution activity in electrolyzing water than a control sample pretreated by conventional pretreatment such as dilute acid, and can work for a long time at a high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hydrogen energy material preparation, and mainly to an electrode and a preparation method and application thereof. Background Art

[0002] With the massive consumption of fossil energy, the energy shortage crisis has gradually become serious. Therefore, it has become urgent to seek clean energy that can replace fossil energy. Hydrogen energy is considered to be one of the cleanest energy sources at present because it has zero carbon emissions during use. There are many ways to obtain hydrogen energy, among which the most promising way is to use renewable energy to generate electricity and then use water electrolysis to produce hydrogen.

[0003] In the process of water electrolysis, the process of oxidizing hydroxide to generate oxygen at the anode end involves four electron transfer, and the electrolysis efficiency is low relative to the cathode end, so it has become a key step restricting the electrolysis of water reaction. In recent years, oxides, hydroxides, sulfides, and phosphides of various transition metals have shown good catalytic water electrolysis oxygen activity, and the performance of bimetallic hydroxides is particularly outstanding, and the preparation method is relatively simple, with less environmental pollution, which has received the focus of scientific researchers. However, it is precisely because the preparation conditions of hydroxides are relatively mild that the surface of the metal substrate is required to be clean, and the substrate needs to be pretreated to remove organic matter or other impurities on the surface. The current common cleaning method for metal substrates is to use acetone, dilute acid, and ethanol to clean in sequence, which can better remove organic matter and oxide layers on the surface of the substrate. However, this method wastes a lot of solvent, and it is difficult to perform soaking and cleaning operations for large-area metal substrates.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide an electrode and a preparation method and application thereof, aiming to solve the problem that the existing pretreatment method of metal substrates requires a large amount of acid and alkali and is difficult to operate on a large scale.

[0006] The technical solution of this application is as follows:

[0007] A method for preparing an electrode, comprising the following steps:

[0008] S1. The metal substrate is placed in a heating device and heated at a low temperature under a calcining atmosphere, kept warm, cooled naturally, washed with water and dried to obtain the activated metal substrate;

[0009] S2. placing the activated metal substrate in a double metal salt mixture to in-situ grow a double hydroxide nanosheet catalyst on the activated metal substrate.

[0010] The metal substrate is subjected to low-temperature heating treatment in a calcining atmosphere to remove surface organic matter and retain the oxide layer, and then a double hydroxide nanosheet catalyst is in situ grown on the metal substrate by immersion at room temperature. The catalyst has a high specific surface area and good catalytic activity, and the catalyst has a strong bonding force with the metal substrate, which can improve the activity and stability of oxygen evolution in water electrolysis at the anode.

[0011] The method for preparing the electrode, wherein in step S1, the temperature of the low-temperature heating is 100-300 degrees Celsius, the temperature rise rate is 2-10 degrees Celsius / minute, and the holding time is 0.5-5 hours. Through this low-temperature heating process, the organic matter or oil on the surface of the metal substrate can be oxidized and removed, and the temperature is controlled within 300 degrees Celsius and the heating time is within 5 hours, which can prevent the metal substrate from becoming brittle.

[0012] The method for preparing the electrode, wherein, in step S1, the metal substrate is a nickel-based substrate;

[0013] In step S1, the calcination atmosphere is air atmosphere or inert atmosphere, and the gas pressure is one atmosphere;

[0014] In step S1, the heating equipment is an oven, a muffle furnace or a tube furnace.

[0015] The method for preparing the electrode, wherein the nickel-based substrate is nickel foam, nickel mesh or nickel fiber felt.

[0016] The electrode preparation method, wherein in step S2, the standing temperature is 20-30° C., and the standing time is 24-72 hours.

[0017] In the method for preparing the electrode, the bimetallic salt mixture is an aqueous solution containing two non-precious metal salts.

[0018] The method for preparing the electrode, wherein the bimetallic salt mixture is a mixture of a nickel salt and an iron salt or a mixture of a nickel salt and a cobalt salt;

[0019] The nickel salt is nickel chloride hexahydrate, the cobalt salt is cobalt nitrate nonahydrate or cobalt chloride hexahydrate, and the iron salt is ferrous chloride tetrahydrate or ferrous sulfate heptahydrate;

[0020] The molar ratio of the nickel salt to the iron salt or the cobalt salt is (5-20):1, and the mass ratio of the nickel salt to water is 1:(20-100).

[0021] The method for preparing the electrode, wherein the nickel salt is nickel chloride hexahydrate, the iron salt is ferrous sulfate heptahydrate, and the cobalt salt is cobalt chloride hexahydrate;

[0022] The molar ratio of the nickel salt to the iron salt or the cobalt salt is (9-11):1, and the mass ratio of the nickel salt to the water is 1:(40-60).

[0023] An electrode, wherein the electrode is prepared by the above-mentioned method for preparing the electrode.

[0024] An application of the electrode as described above, wherein the electrode is used for the preparation of energy storage materials or for oxygen evolution reaction by electrolysis of water.

[0025] Beneficial effect: In the present application, by optimizing the pretreatment method of the metal substrate, a simple-to-operate, solvent-free pretreatment method of the metal substrate is adopted, which can fully remove the organic matter on the metal substrate and activate the metal substrate. Subsequently, a double hydroxide nanosheet catalyst can be grown on the metal substrate by a simple soaking method. The catalyst has a high specific surface area and good catalytic activity, and has a strong binding force with the metal substrate. The electrode prepared by the preparation method of the present application has better oxygen evolution activity in electrolysis of water than the control sample pretreated by conventional pretreatment such as dilute acid, and can work for a long time at a high current density, which has great application prospects. At the same time, the present application is expected to be applied to the preparation of other electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the NiFe LDH / a-Ni felt in Example 1 of the present application.

[0027] Figure 2 This is a scanning electron microscope image of the NiFe LDH / Ni felt in the control sample 1 in Example 1 of the present application.

[0028] Figure 3 This is a comparison chart of the electrochemical performances of NiFe LDH / a-Ni felt, NiFe LDH / Ni felt and Ni felt in Example 1 of the present application.

[0029] Figure 4 This is a comparison chart of constant current test results under high current in Example 1 of the present application, in which NiFe LDH / a-Ni felt and NiFe LDH / Ni felt are used as anodes, respectively, and untreated Ni fiber felt is used as cathode.

[0030] Figure 5 This is a comparison chart of the electrochemical performance of four regions of 10*10 cm NiFe LDH / a-Ni felt in Example 2 of the present application.

[0031] Figure 6 This is a scanning electron microscope image of the 10*10 cm NiFe LDH / a-Ni felt in Example 2 of the present application.

[0032] Figure 7This is a comparison chart of the electrochemical performances of NiCo LDH / a-Ni felt, NiCo LDH / Ni felt and Ni felt in Example 3 of the present application.

[0033] Figure 8 This is a comparison chart of the electrochemical performances of NiFe LDH / a-Ni mesh, NiFe LDH / Ni mesh and Ni mesh in Example 4 of the present application. DETAILED DESCRIPTION

[0034] The present application provides an electrode and a preparation method and application thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0035] Before the present application date, it is generally believed that the organic matter and the impurities such as the oxide layer on the metal substrate surface will affect the catalyst on the metal substrate surface. Therefore, the metal substrate will be pre-treated before the catalyst is prepared on the metal substrate surface, and the organic matter and the impurities such as the oxide layer on the metal substrate surface are removed. The cleaning method of the metal substrate commonly used at present is to clean with acetone, dilute acid, and ethanol in sequence, and the organic matter and the oxide layer on the metal substrate surface can be preferably removed. Further, before the present application date, it is generally believed that the hydroxide preparation conditions are relatively mild, and the metal substrate surface is required to be cleaned, and the metal substrate needs to be pre-treated to remove the organic matter or other impurities on the surface. Existing literature reports that Ni-based substrates are prone to residual oil or organic matter on the surface during production, which easily causes the Ni-based substrate surface to be hydrophobic, resulting in being unable to interact with the soaking liquid, and being difficult to grow hydroxide in situ.

[0036] However, for metal substrates that need to grow hydroxides, the presence of an oxide layer may not necessarily be an obstacle to the growth of hydroxides. Therefore, the applicant has proposed a new pretreatment method for metal substrates used to grow hydroxides, using a non-solvent method to remove only surface organic matter and retain the oxide layer. This may be a more suitable pretreatment method for metal substrates for preparing large-area anodes, which can improve anode performance.

[0037] Specifically, the present application provides a method for preparing an electrode, comprising the following steps:

[0038] S1. Place the metal substrate in a heating device and perform low-temperature heating in a calcining atmosphere, keep the temperature, cool naturally, wash with water and dry to obtain an activated metal substrate.

[0039] S2. placing the activated metal substrate in a double metal salt mixture to in-situ grow a double hydroxide nanosheet catalyst on the activated metal substrate.

[0040] The metal substrate is subjected to low-temperature heating treatment in a calcining atmosphere to remove surface organic matter and retain the oxide layer, and then a double hydroxide nanosheet catalyst is in situ grown on the metal substrate by immersion at room temperature. The catalyst has a high specific surface area and good catalytic activity, and the catalyst has a strong bonding force with the metal substrate, which can improve the activity and stability of oxygen evolution in water electrolysis at the anode.

[0041] Further, in step S1, the metal substrate is a nickel-based substrate. Metal Ni is the most stable in alkaline electrolyzed water, therefore, in the present application, the metal substrate is a nickel-based substrate. The nickel-based substrate can be nickel foam, nickel mesh or nickel fiber felt. Preferably, the nickel-based substrate is nickel fiber felt, which has the advantages of large specific surface area of ​​nickel foam and high mechanical strength of nickel mesh, and is expected to replace nickel mesh as a new generation of electrode substrate.

[0042] In step S1, before low-temperature heating, the metal substrate can be cut as needed to obtain a metal substrate of suitable size. The pretreatment method of the present application only requires the use of heating equipment of suitable size, without considering the corrosion resistance of the container, and without wasting a large amount of acid, which is economical and environmentally friendly.

[0043] In step S1, the temperature of low temperature heating is 100-300 degrees Celsius, the temperature rise rate is 2-10 degrees Celsius / minute, and the holding time is 0.5-5 hours. Through this low temperature heating process, the organic matter or oil on the surface of the metal substrate can be oxidized and removed, and the temperature is controlled within 300 degrees Celsius and the heating time is within 5 hours, which can prevent the metal substrate from becoming brittle. The calcination atmosphere can be an air atmosphere or an inert atmosphere, the inert atmosphere can be an argon atmosphere, etc., and the air pressure can be one atmosphere.

[0044] Preferably, the metal substrate is placed in the middle of the heating device to ensure that the actual heating temperature of the metal substrate is the set temperature of the heating device as much as possible.

[0045] The heating device can be an oven, a muffle furnace or a tube furnace. If heating is required under an inert atmosphere, only a tube furnace can be selected. Preferably, the heating device can be a tube furnace.

[0046] In step S1, when washing with water and drying, the drying can be natural drying at room temperature, which is simple to operate.

[0047] In step S2, the bimetallic salt mixture is an aqueous solution containing two non-precious metal salts, and the anode catalyst uses a high-valent non-precious metal hydroxide, which can reduce the energy barrier of oxidizing hydroxide and reduce the overpotential required for electrolysis of water. The non-precious metal salt can be a nickel salt, an iron salt or a cobalt salt. Further, the bimetallic salt mixture can be a mixture of a nickel salt and an iron salt, a mixture of a nickel salt and a cobalt salt, etc.

[0048] The nickel salt may be nickel chloride hexahydrate, the cobalt salt may be cobalt nitrate nonahydrate or cobalt chloride hexahydrate, and the iron salt may be ferrous chloride tetrahydrate or ferrous sulfate heptahydrate.

[0049] Preferably, the nickel salt is nickel chloride hexahydrate, the iron salt is ferrous sulfate heptahydrate, and the cobalt salt is cobalt chloride hexahydrate. These three compounds are relatively stable.

[0050] The molar ratio of nickel salt to iron salt or cobalt salt is (5-20):1. The use of the metal salt in the above specific ratio can improve the catalytic performance of the double hydroxide. The mass ratio of nickel salt to water is 1:(20-100). The use of this specific concentration can ensure that the concentration of the metal salt is moderate, avoiding the metal salt concentration being too dilute, resulting in a slow in-situ growth rate of the hydroxide, and avoiding the metal salt concentration being too concentrated, which is easy to grow too thick hydroxide and affect the conductivity.

[0051] Preferably, the molar ratio of nickel salt to iron salt or cobalt salt is (9-11):1. The catalytic performance of the double hydroxide prepared by using the metal salts in this specific ratio is better.

[0052] Preferably, the mass ratio of nickel salt to water is 1:(40-60). Using this concentration range of metal salt, the catalytic performance of the prepared double hydroxide is better.

[0053] In step S2, the standing temperature may be 20-30°C, and the standing time may be 24-72 hours.

[0054] In step S2, after standing still, the metal substrate is taken out from the double metal salt mixture, washed with water for several times, and dried naturally.

[0055] In the present application, by optimizing the pretreatment method of the metal substrate, a simple-to-operate, solvent-free pretreatment method of the metal substrate is adopted, which can fully remove the organic matter on the metal substrate and activate the metal substrate. Subsequently, a double hydroxide nanosheet catalyst can be grown on the metal substrate by a simple soaking method. The catalyst has a high specific surface area and good catalytic activity, and has a strong binding force with the metal substrate. The anode prepared by the preparation method of the present application has a better oxygen evolution activity in electrolyzed water than the control sample pretreated by conventional methods such as dilute acid, and can work for a long time at a high current density, which has great application prospects. At the same time, the present application is expected to be applied to the preparation of other electrode materials.

[0056] In the present application, an electrode is also provided, and the anode is prepared by using the above-mentioned electrode preparation method.

[0057] In the present application, an application of an electrode is also provided, wherein the electrode is used for preparing an energy storage material. Furthermore, the electrode is used for electrolysis of water to generate oxygen.

[0058] The invention is further described below by means of specific examples.

[0059] Example 1

[0060] Step 1: Cut 2*5cm Ni fiber felt and place it in a tubular furnace without sealing. Heat the temperature from room temperature to 200℃ at a rate of 10℃ per minute and keep it warm for 1 hour. After the insulation, cool it naturally, wash the Ni fiber felt with pure water, and dry it naturally.

[0061] Step 2: Place the pretreated Ni fiber felt in 50 ml of aqueous solution in which 1.19 g NiCl2•6H2O and 0.15 g FeSO4•7H2O have been dissolved in advance, soak it at 25°C for 24 hours, take out the Ni fiber felt, wash it with pure water three times, and dry it naturally to obtain NiFe LDH / a-Ni felt.

[0062] Control sample 1:

[0063] Step 1: Cut 2*5cm Ni fiber felt, ultrasonically treat it in acetone, 6M HCl and ethanol for 10 minutes respectively, and finally wash it with pure water and dry it naturally.

[0064] The second step is consistent with the second step in Example 1, and NiFe LDH / Ni felt is obtained.

[0065] Figure 1 The scanning electron microscope image of the final product obtained in Example 1 is shown in FIG. Figure 1 It can be seen that NiFe LDH / a-Ni felt is loaded with dense hydroxide nanosheets with a thickness of about 50-150nm, which are basically grown vertically.

[0066] Figure 2 is a scanning electron microscope image of the final product of control sample 1 in Example 1, from Figure 2 It can be seen that the final product of the metal substrate pretreated by traditional methods also loads hydroxide nanosheets, but its density is not as good as NiFe LDH / a-Ni felt.

[0067] The activity of NiFe LDH / a-Ni felt, NiFe LDH / Ni felt and Ni fiber felt in electrolyzing water and releasing oxygen was tested. The results are as follows: Figure 3 As shown, the three curves are divided into the electrochemical performance curves of NiFe LDH / a-Ni felt, NiFe LDH / Ni felt, and Ni fiber felt from top to bottom. Figure 3It can be seen that the activity of NiFe LDH / a-Ni felt in electrolyzing water and oxygen evolution is better than that of NiFe LDH / Ni felt, and is far better than that of Ni fiber felt substrate without growing hydroxide catalyst. Among them, the electrochemical test conditions are: 95°C, 30wt% KOH. The working electrode is hydroxide, the reference electrode is Hg / HgO, and the counter electrode is a platinum electrode. First, a cyclic voltammetry test is performed on the working electrode to achieve the activation effect. The scanning range is 0.8V~1.7V vs RHE, the scanning rate is 0.1V / s, and the test is stopped when the electrode is stable. Then the electrochemical activity of the electrode is tested using linear scanning voltammetry. The scanning range is 1.2V~1.7V vs RHE, and the scanning rate is 5mV / s.

[0068] NiFe LDH / a-Ni felt and NiFe LDH / Ni felt were used as anodes, and untreated Ni fiber felt was used as cathode. Constant current test was carried out under high current. The results are shown in Figure 4. The two curves are respectively the curves of NiFe LDH / Ni felt and NiFe LDH / a-Ni felt from top to bottom. Figure 4 It can be seen that the performance of NiFe LDH / a-Ni felt does not decay when used for more than 24 hours at a high current density, indicating that NiFe LDH / a-Ni felt has good chemical stability. Among them, the constant current test conditions are: 95℃, 30wt% KOH. The working electrode is hydroxide, and the counter electrode is untreated Ni felt. The current is set to 0.6A and the test is 160 hours.

[0069] Example 2

[0070] The first step is to cut a 10*10 cm Ni fiber felt and place it in a tubular furnace. The remaining steps are the same as in Example 1.

[0071] Step 2: Place the pretreated Ni fiber felt in 500 ml of aqueous solution in which 5.95 g NiCl2•6H2O and 0.75 g FeSO4•7H2O have been dissolved in advance, soak it at 25°C for 24 hours, take out the Ni fiber felt, wash it three times with pure water, and dry it naturally.

[0072] After testing the electrochemical performance of four sites in the large-area electrode, it was found that the performance test results of the electrodes obtained in Example 1 and Example 2 were basically similar, and both could reach 1200 mA cm at 1.7 V. -2 ,like Figure 5 As shown, the electrochemical performance curves of the four sites are respectively shown. Among them, the electrochemical test conditions and process are the same as those in Example 1.

[0073] Figure 6This is a scanning electron microscope image of the final product obtained in Example 2. Compared with the electrodes obtained in Example 1 and Example 2, there is only a slight difference in the density of the double hydroxide nanosheet catalyst on the electrode surface.

[0074] Example 3

[0075] The first step is the same as the first step in Example 1.

[0076] Step 2: Place the pretreated Ni fiber felt in 50 ml of aqueous solution in which 1.19 g NiCl2•6H2O and 0.119 g CoCl2•6H2O have been dissolved in advance, soak it at 25°C for 24 hours, take out the Ni fiber felt, wash it with pure water three times, and dry it naturally to obtain NiCo LDH / a-Ni felt.

[0077] Control sample 2: Step 1: Cut 2*5 cm Ni fiber felt, ultrasonicate it in acetone, 6M HCl and ethanol for 10 minutes respectively, and finally wash it with pure water only and dry it naturally.

[0078] The second step is consistent with the second step in Example 3 to obtain NiCo LDH / Ni felt.

[0079] The activity of NiCo LDH / a-Ni felt, NiCo LDH / Ni felt and Ni fiber felt in electrolyzing water and releasing oxygen was tested. The results are as follows: Figure 7 As shown, the three curves are divided into the electrochemical performance curves of NiCo LDH / a-Ni felt, NiCo LDH / Ni felt, and Ni fiber felt from top to bottom. Figure 7 It can be seen that the activity of NiCo LDH / a-Ni felt in electrolyzing water and oxygen evolution is better than that of NiCo LDH / Ni felt, and is also better than that of Ni fiber felt without growing hydroxide catalyst. Among them, the electrochemical test conditions are: 95°C, 30wt% KOH. The working electrode is hydroxide, the reference electrode is Hg / HgO, and the counter electrode is a platinum electrode. First, a cyclic voltammetry test is performed on the working electrode to achieve the activation effect. The scanning range is 0.8V~1.7V vs RHE, the scanning rate is 0.1V / s, and the test is stopped when the electrode is stable. Then the electrochemical activity of the electrode is tested using linear scanning voltammetry, with a scanning range of 1.2V~1.7V vs RHE and a scanning rate of 5mV / s.

[0080] Example 4

[0081] Step 1: Cut a 2*5 cm single wire Ni mesh with a thickness of 500 nm and place it in a tubular furnace without sealing. Heat it from room temperature to 200°C at a rate of 10 degrees per minute and keep it warm for 1 hour. After the insulation, cool it naturally, clean the Ni mesh with pure water, and dry it naturally.

[0082] Step 2: The same as the second step in Example 1, to obtain NiFe LDH / a-Ni mesh.

[0083] Control sample 3: Step 1: Cut a 2*5 cm single-filament Ni mesh with a thickness of 500 nm, ultrasonicate it in acetone, 6M HCl and ethanol for 10 minutes respectively, and finally rinse it with pure water only and dry it naturally.

[0084] The second step is consistent with the second step in Example 4, and a NiFe LDH / Ni mesh is obtained.

[0085] The activity of NiFe LDH / a-Ni mesh, NiFe LDH / Ni mesh and Ni mesh in electrolyzing water and releasing oxygen was tested. The results are as follows: Figure 8 As shown, the three curves are divided into the electrochemical performance curves of NiFe LDH / a-Ni mesh, NiFe LDH / Ni mesh, and Ni mesh from top to bottom. Figure 8 It can be seen that the activity of NiFe LDH / a-Ni mesh in electrolyzing water and evolving oxygen is better than that of NiFe LDH / Ni mesh, and is far better than that of the Ni mesh substrate without growing hydroxide catalyst, indicating that the substrate pretreatment method of the present application is applicable to a variety of Ni-based substrates.

[0086] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.

Claims

1. A method for preparing an electrode, characterized in that: The following steps are involved: S1. The metal substrate is pretreated by placing the metal substrate in a heating device and heating it at a low temperature under a calcining atmosphere, keeping the temperature, cooling it naturally, washing it with water and drying it to obtain an activated metal substrate, wherein the metal substrate retains an oxide layer; S2. placing the activated metal substrate in a double metal salt mixture to in situ grow a double metal hydroxide nanosheet catalyst on the activated metal substrate; In step S1, the temperature of the low-temperature heating is 100-300 degrees Celsius, the temperature rise rate of the low-temperature heating is 2-10 degrees Celsius / minute, and the insulation time is 0.5-5 hours; In step S2, the standing temperature is 20-30°C, and the standing time is 24-72 hours.

2. The method for preparing an electrode according to claim 1, characterized in that: In step S1, the metal substrate is a nickel-based substrate; In step S1, the calcination atmosphere is air atmosphere or inert atmosphere, and the gas pressure is one atmosphere; In step S1, the heating equipment is an oven, a muffle furnace or a tube furnace.

3. The method for preparing an electrode according to claim 2, characterized in that: The nickel-based substrate is nickel foam, nickel mesh or nickel fiber felt.

4. The method for preparing an electrode according to claim 1, characterized in that: The double metal salt mixed solution is an aqueous solution containing two non-noble metal salts.

5. The method for preparing an electrode according to claim 4, characterized in that: The bimetallic salt mixture is a mixture of nickel salt and iron salt or a mixture of nickel salt and cobalt salt; The nickel salt is nickel chloride hexahydrate, the cobalt salt is cobalt nitrate nonahydrate or cobalt chloride hexahydrate, and the iron salt is ferrous chloride tetrahydrate or ferrous sulfate heptahydrate; The molar ratio of the nickel salt to the iron salt or the cobalt salt is (5-20):1, and the mass ratio of the nickel salt to water is 1:(20-100).

6. The method for preparing an electrode according to claim 5, characterized in that: The nickel salt is nickel chloride hexahydrate, the iron salt is ferrous sulfate heptahydrate, and the cobalt salt is cobalt chloride hexahydrate; The molar ratio of the nickel salt to the iron salt or the cobalt salt is (9-11):1, and the mass ratio of the nickel salt to the water is 1:(40-60).

7. An electrode, characterized in that: The electrode is prepared by the method for preparing the electrode as described in any one of claims 1 to 6.

8. Use of the electrode as claimed in claim 7, characterized in that: The electrode is used for preparing energy storage materials or for electrolyzing water and oxygen evolution reaction.

Citation Information

Patent Citations

  • Bifunctional electrocatalytic material and preparation method and application thereof

    CN111672514A

  • Cerium-modified molybdenum disulfide bifunctional catalyst as well as preparation and application thereof

    CN115584530A